Cognitive coping style (monitoring and blunting) and the need for information, information satisfaction and shared decision making among patients with haematological malignancies. Issue 5 (21st October 2014) - Rood, Janneke A. J.; Van Zuuren, Florence J.; Stam, Frank; van der Ploeg, Tjeerd; Huijgens, Peter C.; Verdonck‐ de Leeuw, Irma M.
Abstract Objective A haematological malignancy is a serious, life‐altering disease and may be characterised as an uncontrollable and unpredictable stress situation. In dealing with potentially threatening information, individuals generally utilise two main cognitive coping styles: monitoring (the tendency to seek threat‐relevant information) and blunting (avoiding threatening information and seeking distraction). The aim of this study was to obtain insight into the association between cognitive coping style and (a) need for information, (b) satisfaction with information, (c) involvement in decision making, and (d) quality of life (QoL). Methods In this cross‐sectional study, coping style was assessed among adult patients diagnosed with a haematological malignancy, using an adapted version of the Threatening Medical Situations Inventory. Information need, information satisfaction, decision‐making preference and QoL were measured with validated questionnaires. Results In total, 458 patients returned the questionnaire (66%). A monitoring coping style was positively related to need for both general and specific information. Blunting was positively and QoL was negatively related to need for information. Monitoring was positively related to involvement in decision‐making and negatively to information satisfaction. Using multivariate analysis, this relation between monitoring and information satisfaction disappeared, and for blunting, we found a negatively significant relation. QoL was not related to coping style. Conclusions Among patients with haematological malignancies, coping style is related to a need for information, information satisfaction, and involvement in treatment decision‐making. Therefore, it is important for health care professionals to be aware of individual differences in cognitive coping style. Copyright © 2014 John Wiley & Sons, Ltd.